CONTRIBUTION OF BUNGUS OCEAN FISHING PORT TO THE REGIONAL ECONOMY (ALBACORE Jurnal Penelitian Perikanan Laut, 2025)
The Bungus Fishing Port serves as a center for fishery economics in the West Sumatra region and its surroundings, expected to contribute to the regional economy of West Sumatra. However, empirically, the contribution of this port has not yet been determined. In actuality, this data is crucial as a foundation for the development of the fishing port, both in terms of its administration and its interaction with the neighborhood. Therefore, the purpose of this research is to calculate the magnitude of Bungus FP, contribution to the local economy. The method used in this research is a descriptive method, a methodological approach aimed at presenting and interpreting research objects objectively. Data collection was conducted through literature studies, field observations, and interviews with all business actors at Bungus FP. Purposive sampling was used to identify respondents. The data was analyzed using a descriptive comparative method, which involves comparing the economic value at the fishing port with the GDP (Gross Regional Domestic Product) at the level of Padang City, West Sumatra Province, and the National level. The results indicate that economic activities in the PPS Bungus area consist of various types of businesses such as restaurants, ship supplies, fishermen, ship docking, processors, street vendors, and others, with a total annual income of IDR 815,256,218,383. The contribution of PPS Bungus to the Fishery GDP and the overall GDP of Padang City in 2024 is 19.55% and 0.97%, respectively.Key words: bungus, economy, contribution, fishing port, region